Deformation and Failure Mechanism of the Lower Roadway in a Close-Range Residual Coal Pillar Area - Wang, Xiao-He; Zhao, Zhi-Qiang; Wu, Zheng; Zhang, Hao-Hao; Wang, Jun; Sui, Yi; Ren, Zhi-Cheng (Frontiers in Earth Science, 2022)
In order to demonstrate the deformation and damage mechanism of lower roadway in close-range residual coal pillar area, this paper takes the Tashan Coal Mine as the research background. We used the roof drilling peephole technology to detect the damage of the roof surrounding rock of the roadway roof, and based on the theory of butterfly plastic zone, We derive the boundary invisibility equation for the plastic zone of a circular hole in a non-uniform stress field where the principal stress is at an arbitrary angle to the vertical.Then we use the Maple mathematical drawing software combined with the FLAC3D numerical simulation software to discuss the influence of the principal stress ratio and the principal stress direction on the plastic zone of the roadway. The results demonstrate two things: when the bidirectional stress ratio is large, the plastic zone of the surrounding rock of the roadway presents a butterfly shape, and the direction of the butterfly-shaped failure of the roadway is related to the direction of the principal stress. Then we combined with the field test images, we explain that the asymmetric damage pattern of the lower roadway in close-range residual coal pillar area is due to the roadway being in a non-uniform stress field and the main stress direction being deflected.